A Direct Observational Measure of Family Functioning for a Low-Resource Setting: Adaptation and Feasibility in a Kenyan Sample. Issue 2 (March 2019) - Giusto, Ali; Kaiser, Bonnie N.; Ayuku, David; Puffer, Eve S.
Abstract: Family interactions are recognized as highly influential for youth development of psychopathology. Key challenges for assessing family functioning include cross-cultural variability in functioning and self-report measurement challenges. Observational measures—adapted to cultural context—provide an approach to addressing challenges. This study aimed to adapt a direct observational tool for assessing family interaction patterns in Kenya, to outline a replicable adaptation process, and to explore tool feasibility and acceptability. We reviewed existing tools to assess their adaptability based on compatibility with context-specific data. After initial modifications, the measure was iteratively adapted through pilot testing and collaborative discussions between U.S. and Kenyan collaborators that drove changes and further piloting. The measure was administered to 26 families. The Family Problem Solving Code was chosen for adaptation. The tool's activity structure was feasible to administer, but activity content showed low acceptability, requiring new content. Final activities included (a) a hands-on problem-solving task, (b) a discussion of marital conflict with couples, and (c) a structured discussion of family hopes. Codes were adapted to reflect culturally congruent descriptions of behavior, expressions, and interactions, including an emphasis on nonverbal interactions. The scoring system was modified to facilitate training and consistent rating among trainees with limited experience. Observational tool findings were consistent with those of an interview assessing family functioning, rated by clinical and non-clinical raters. Adaptation resulted in a culturally relevant tool assessing family functioning that proved feasible and acceptable. The adaptation process also proved feasible and efficient in a low-resource setting, suggesting its utility for other contexts. Highlights: Observational assessment of family functioning was feasible and acceptable in Kenya Existing tools can be adapted for diverse, low-resource settings The adapted tool changed to capture context-specific functioning